An example of modeling the combined effects of creep and fatigue loading in musculoskeletal tissue. (November 2019) - Gallagher, Sean; Huangfu, Rong
Human musculoskeletal tissues incur both creep and cyclic loading every day, both of which can contribute to cumulative damage development. This paper will describe methods of understanding and modeling the interaction of creep and fatigue loading. Results indicate that at very low levels of stress, creep loading may be the predominant mechanism of damage in tissues; however, fatigue loading becomes the strongly dominant mechanism of damage at levels above this.